Acute coronary syndrome in a patient with Eisenmenger's syndrome. (5th December 2013) - Prakash, S S; Gupta, Kamal; Agrawal, Navin; Shankar, S
Abstract : Eisenmenger's syndrome is a complex multisystem disease which occurs as a consequence of large left to right shunt affecting the pulmonary vasculature causing suprasystemic pulmonary artery pressures and subsequent right to left shunt. Usually Eisenmenger's syndrome is characterised by coronary artery dilation but coronary artery disease and occurrence of acute coronary syndrome is a rare association seldom described in literature. We present the case of a 33-year-old man who presented with an anterior wall ST elevation mycocardial infarction and was thrombolysed. The occurrence of acute coronary event in a case of Eisenmenger's syndrome is a rare event and needs to be discussed and kept in mind by physicians and cardiologists who deal with such cases so that a high index of suspicion may be developed and emergent management may be possible.